Hubungan Pengasuhan Digital Dengan Intensitas Penggunaan Gadget Pada Anak Usia 5-6 Tahun Di Kelurahan Sidomulyo Timur Kota Pekanbaru - Regina Maharani; Yeni Solfiah; Nurlita Nurlita (Departement of Mathematics Education, 2023)
The purpose of this research was to determine the relationship between digital parenting and the intensity of using gadgets in children aged 5-6 years in Sidomulyo Timur Village, Pekanbaru City. The type of research used is correlation research. The population and research sample are 88 parents. The steps taken in this comparative research are: identifying potentials and problems, gathering information, determining data collection methods, data collection, data analysis, and concluding data. Data collection techniques in this study are by means of questionnaires and documents. The data analysis technique used for this research is the chi square method. Based on calculations from several tests conducted, it provides scientific evidence that there is a relationship between digital parenting and the intensity of using gadgets in children aged 5-6 years in Sidomulyo Timur Village, Pekanbaru City.